Measurement Method of Comprehensive Transportation Development Quality Based on Transportation Efficiency - Jiahao Zhan; Shengwen Yang; Xueyin Wang; Ting Fan (Journal of Advanced Transportation)
Transportation is the forerunner of economic and social development. Therefore, the high-quality development of comprehensive transportation is of great significance to ensure overall economic and social progress and the smooth implementation of major national strategies. The essence of high-quality development in transportation is to realize the optimal allocation of transportation resources. This study handles two aspects. First, the factors that reflect the quality of comprehensive transportation development are defined and analyzed, and an evaluation system is proposed to build China’s comprehensive transportation development quality with transportation efficiency as the core is proposed, taking into account transportation infrastructure and transportation scale. Second, the static comprehensive evaluation value is calculated by the entropy weight method, and then the incentive control model is constructed by introducing incentive factors to achieve a dynamic comprehensive evaluation of comprehensive transportation development. The research results not only propose new indicators but also evaluate different modes of transportation within the same dimension. The results show that the quality of comprehensive transportation development in China is generally on the rise, but there are obvious regional differences. The proposed model is derived from evaluation cases in transportation-related fields and has not yet been applied in the transportation field. It can help understand the development status of the industry and assist in policy formulation.